2015
DOI: 10.4067/s0034-98872015000100001
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos en la terapia farmacológica de la enfermedad inflamatoria intestinal

Abstract: Background: The purpose of inflammatory bowel disease (IBD) treatment is to achieve resolution of symptoms and remission of disease with a minimum of adverse events (AE (Rev Med Chile 2015; 143: 7-13)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
3
10
0
2
Order By: Relevance
“…Currently, IBD treatment primarily focuses on immunosuppressive therapies involving biologicals, corticosteroids and immunomodulators [ 6 , 7 , 8 ]. However, the side effects of these treatments limit their therapeutic potential [ 8 , 9 , 10 , 11 ]. Hence, there is an urgent need for pragmatic treatment options targeting the multifactorial recurrent inflammatory cascade to mitigate chronic intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, IBD treatment primarily focuses on immunosuppressive therapies involving biologicals, corticosteroids and immunomodulators [ 6 , 7 , 8 ]. However, the side effects of these treatments limit their therapeutic potential [ 8 , 9 , 10 , 11 ]. Hence, there is an urgent need for pragmatic treatment options targeting the multifactorial recurrent inflammatory cascade to mitigate chronic intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that there was considerable improvement in hair condition. On the other hand, a recent study 16 showed the development of AA in 5 out of 146 patients with IBD while they were receiving azathioprine. Our case may be the first to document the response of alopecia universalis to azathioprine in a patient with UC.…”
Section: Discussionmentioning
confidence: 95%
“…The pathogenesis of IBD is not completely defined, but recently the spotlight is on microbiota-stimulated immunoreactivity and adipose tissue hormonal dysregulation (Kostic et al, 2014; Schaubeck and Haller, 2015). What is more important, the currently available treatment includes 5-aminosalicylates, steroids, biological therapy and surgical procedures—all aggressive and with significant side effects (George et al, 2015; Khanna and Feagan, 2015; Meyer et al, 2015). Thus, it is crucial to seek new agents that could influence the clinical course of IBD and alleviate or prevent exacerbations.…”
Section: Pufas In Inflammatory Bowel Diseasesmentioning
confidence: 99%